Solar drying technology for post-harvest loss management of horticulture products: Findings from baseline survey in Nigeria - Balana, Bedru; Popoola, Olufemi; Yamauchi, Futoshi; Olanipekun, Caleb; Totin, Edmond; Salaudeen, Kamaldeen Oladimeji; Muhammad, Aminu; Shi, Weilun; Liu, Yanyan (International Food Policy Research Institute, 2024)
Creating a sustainable food system requires addressing the critical challenges of food waste and loss. This is particularly crucial for small-scale farmers who supply local markets but lack access to modern preservation technologies, leading to significant product losses between harvesting and selling. Research indicates that in low-and middle-income countries, approximately 38 percent of harvested perishable agricultural goods are lost before consumption. Globally, about 22 percent of fruits and vegetables are lost in the supply chain before reaching retailers (FAO, 2019). These postharvest losses have significant impacts to low economic return and household food and nutrition security. Post-harvest losses also contribute significantly to environmental concerns, accounting for roughly 8 percent of yearly global greenhouse gas emissions. Among all food categories, fruits and vegetables experience the highest losses by weight.